The Application of Wahdah Method in Memorizing the Qur'an for Students of SMPN 1 Unggul Sukamakmur - Wahyu Khafidah; Wildanizar Wildanizar; Tabrani ZA; Nurhayati Nurhayati; Zubeir Raden (Universitas Muhammadiyah Yogyakarta, 2020)
This study used a quantitative approach. The population in this study were 400 students in SMPN 1 Unggul Sukamakmur, while the number of teachers teaching Islamic education subject was 5 people. Since the population was too large, the objects of research were 5 Islamic education teachers, 40 students (10% of the population), and the principal of SMP N 1 Unggul Sukamakmur. Based on the results of interviews with Islamic education teachers, the researchers could see that they have been familiar and mastered the